Effects of Two Commercial Protein Diets on the Health of Two Imago Ages of Apis mellifera L. Reared in Laboratory - Simona Sagona; Francesca Coppola; Antonio Nanetti; Elena Tafi; Lionella Palego; Laura Betti; Gino Giannaccini; Antonio Felicioli (Animals, 2022)
Protein-supplemented artificial diets are widely used by beekeepers during winter and whenever food availability is low, yet no data are available concerning their effects on bees’ health. In this work, the effects of two commercial diets enriched with 1.7% and 7.7% protein concentration on feed intake, survival rate, glucose oxidase, phenoloxidase and glutathione S-transferase in newly emerged and forager bees were tested. Administration of a 7.7% protein-enriched diet significantly reduced the lifespan of both newly emerged and forager bees, while only in foragers a significantly higher feed intake was recorded. In newly emerged bees, administration of a high-protein-enriched diet stimulated glucose oxidase production at the 10th day of feeding, determined a reduction of phenoloxidase and did not affect glutathione S-transferase activity. In forager bees, a high level of protein inclusion did not determine any significant variation in either glucose oxidase, phenoloxidase or glutathione S-transferase activity. Therefore, the results obtained in this investigation suggest that administration of commercial protein diets negatively affect honey bee health, determining an increase in mortality. Further investigations on the effect of concentration and quality of proteins are desirable to provide beekeepers with scientific evidence on protein feeding.